PEMASARAN BARANG DAN JASA DALAM PERSPEKTIF UNDANG-UNDANG ANTI MONOPOLI - Ida Bagus Radendra Suastama; Ida Ayu Komang Juniasih (Forum Manajemen STIMI Handayani Denpasar, 2018)
This research aims is knowing, identifying, and inventing the issues shouldbe recognized by business actors in implementing their marketing activities, mainlyin relation with the Indonesian prevailing regulations regarding Anti Monopoly.This is a qualitative research. As many times stated by literatures on the researchmethodology, it is necessary to be restated here that Qualitative Research is theresearch that endeavoring to find the core or essential meanings or ideas that laidbehind a social action or phenomenon.What is meant as phenomenon in this contextis the values laid behind or basing the stipulation of Indonesian Anti MonopolyLaw. This research has come to conclusions as follows : That the issues should beconcerned and obeyed by the business actors in performing or implementing the marketing of goods and/or services are understanding and preventing from breaching the regulations contained in The Law on Anti Monopoly, which include, amongothers : oligopoly, price fixing, region division, boycott, kartel, trust, oligopsony,vertical integration, closed agreement, agreement with foreign parties, monopoly,monopsony, market controlling, and conspiracy. This research also provides somerecoomendations that could be used by the Business Actors to prevent them from legalproblems caused by marketing activities that break the Indonesian Anti MonopolyLaws.